Пошаговое объяснение:
1) 1 5/7 + 3 2/7 =
4 7/7 = 5
2) 4 3/7 - 6/7 = 31/7 - 6/7 = 25/7 = 3 4/7
3) 5 - 3 4/7 = 4 7/7 - 3 4/7 = 1 3/7
1) 1 5/7+3 2/7=4 7/7=5
2) 4 3/7-6/7=31/7-6/7=25/7
3) 25/7=3 4/7
4) 5-3 4/7=4 7/7-3 4/7=1 3/7
ответ: 1 3/7
правильно, проверено.
Пошаговое объяснение:
1) 1 5/7 + 3 2/7 =
4 7/7 = 5
2) 4 3/7 - 6/7 = 31/7 - 6/7 = 25/7 = 3 4/7
3) 5 - 3 4/7 = 4 7/7 - 3 4/7 = 1 3/7
1) 1 5/7+3 2/7=4 7/7=5
2) 4 3/7-6/7=31/7-6/7=25/7
3) 25/7=3 4/7
4) 5-3 4/7=4 7/7-3 4/7=1 3/7
ответ: 1 3/7
Пошаговое объяснение:
правильно, проверено.